Assessment of vertical transportation system in oldest shopping mall / Muhammad Rasul Ahmad Nasir - Ahmad Nasir, Muhammad Rasul (Faculty of Architecture, Planning and Surveying, 2015)
Vertical transportation system in oldest shopping mall is very important to make sure the system such as elevator are functional and can transport occupants efficiently. Besides, assessment work or activities cannot separate with"the involvement of cost which sometimes high depends to type of damages occur. Maintenance work of vertical transportation system is more focus to inspection, repairing, security, and others aspect such as the satisfaction of elevator user. Meanwhile, there are four objectives to achieve above aims are to understand the management of the vertical transportation system in oldest shopping mall, to know the level of satisfaction of the users regarding the maintenance for vertical transportation system in oldest shopping mall, to identify the problem and effectiveness of vertical transportation system maintenance in oldest shopping mall and to analyze and recommend a comprehensive maintenance approach for vertical transportation system. Scope of study is focus on assessment of vertical transportation system in oldest shopping mall. Interviews session and observation was conducted by the author to achieve aim and objectives. Interviews session was also involved the parties from elevator contractor. Based on data analysis, vertical transportation system in oldest shopping mall mostly using out-source practice of elevator contractor. Usually, out-source contractor will quote for the highest maintenance cost, not produce the best quality of maintenance work, and take time for process find out-source contractor. Overall, the most of user are unsatisfied of vertical transportation system in oldest shopping mall. This is may be done to required performance of the elevator is up to expectation standard.